The Effect of Internal Control, Human Resource Competence, Audit Activities on the Effectiveness of the Use of Village Funds - Maruwah, Intan Nur; Putri, Adinda Felisa; Rosnidah, Ida; Salta, Salta (Jurnal Ekuisci, 2025)
Background. The performance of village officials in managing the village budget has a significant impact on the effective utilization of village funds. Indonesian: According to Law No. 16 of 2019 from the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia, programs or activities related to the empowerment and development of village communities are prioritized when using all village funds. Aims. The purpose of this study is to investigate the impact of internal control, human resource competence, and audit practices on the effectiveness of village funds utilization in Village X, District X, Majalengka Regency. The efficiency of village funds is a dependent variable that is analyzed, while internal control, human resource competence, and audit activities are independent factors that are examined. Methods. This study uses a quantitative methodology. Approximately 100 households were given questionnaires to complete, allowing for the collection of data. The impact of independent and dependent factors on the efficiency of village budget utilization was then determined using multiple regression analysis to test the data. Result. The findings show that the efficiency of village budget utilization is significantly influenced by internal control, human resource competence, and audit activities. To expand our understanding of the relationships between the variables that have been studied. Conclusion. The results of this research will help village officials in improving the quality of their performance, for local governments are expected to be able to support by providing resources that have special competencies in their respective fields. Implementation. This research adds to the global understanding of best practices in public financial management at the local level, particularly in developing countries with similar village fund schemes